Pengaruh Kajian Tasawuf KH. Moch. Djamaluddin Ahamad Terhadap Perilaku Masyarakat Desa Sambong Dukuh - Ruth Nilam Apsari; Umi Chaidaroh; Hilyah Ashoumi (JoEMS (Journal of Education and Management Studies), 2020)
With the development of increasingly advanced science and technology, it is deemed necessary to also be balanced with praiseworthy behavior, in this case science and technology can make people forget themselves, which in turn will harm their lives. So in this case, knowing God is one of the best ways to filter ourselves, which ultimately can organize our hearts so that they always have good behavior towards all living things. This article discusses the themes surrounding Sufism Study, the behavior of the Sambong Dukuh villagers and also the relationship between the two. From the research conducted by the author, the writer takes one of the leading religious figures named KH. Moch. Djamaluddin Ahmad, who also became a practitioner in the field of Sufism, which was located in the Sambong Hamlet area. The author takes this theme with several objectives, namely to find out Sufism Study KH. Moch. Djamaluddin Ahmad, Sambongdukuh Village Community Behavior and also know the influence of KH Sufism study. Moch. Djamaluddin Ahmad towards the behavior of the people of Sambongdukuh Village. In this study the authors conducted a quantitative approach in which the results would later be in the form of validity of the data that had been collected and analyzed, to find out the results of the data had an effect or not, the authors conducted data analysis with data collection procedures. To process the data, the writer needs a data source. Sources of data obtained by observing, conducting interviews and distributing questionnaires. Based on the results of the data that has been obtained and the data has been processed with the formula that has been determined, this study provides results as much as 10.8% of the study has an influence on the behavior of the people of Sambong Hamlet. And this study was accepted by the Jombang community in general, especially the village of Sambong Dukuh in particular